The effect of communication technology adoption on inventory management and firm performance - Nguyen, Van Bay; Nguyen, Thanh Cuong; Phan, Thanh Hai (Journal of Finance - Marketing Research, 2025)
The study examines the effect of inventory management and the adoption of communication technology on the performance of firms in Vietnam's manufacturing industry and attempts to fill a research gap regarding the impact of these two variables on each other in emerging economies. In order to examine the effect, panel data from 2013 to 2023 have been used and SGMM estimator has been utilized to capture the dynamics between the investigated variables. The study shows that the adoption of inventory management and the use of communication technology positively affect the performance of firms as measured by ROA and ROE. Besides, there is an interaction between these variables which increases the effect of each variable on firm performance. The study further shows that some of the proxies for the adoption of communication technology (advertising expense, value of intangible technology asset, and capital expenditure) contribute significantly to performance improvement. The results are consistent with Resource Based View and Dynamic Capabilities Theory emphasizing the role of resource integration.